DESAIN PEMBELAJARAN TECHNOPRENEURSHIP UNTUK MENINGKATKAN MOTIVASI BERWIRAUSAHA MAHASISWA UNISKA KEDIRI - Lina Saptaria; Wawan Herry Setyawan (Prima Magistra: Jurnal Ilmiah Kependidikan, 2021)
During the Covid 19 pandemic, entrepreneurship learning activities in universities were carried out boldly. This is a challenge for lecturers to design technology-based entrepreneurship learning that can increase student motivation in entrepreneurship. The purpose of this study was to produce a technopreneurship learning design model for UNISKA Kediri students with a scientific approach. This type of research is a development research using the 4D model consisting of: define, design, develop, and disseminate. The stages of research activities consist of: 1) problem problems, needs analysis and learning analysis; 2) scientific technopreneurship cooperation approach; 3) scientific technopreneurship business plan design; 4) products (prototypes of goods or services), 5) job evaluation. The results showed that the technopreneurship learning design was very feasible to use. From the measurement results of the three expert validators, the measurement results (p) is greater than or equal to 3.93 and less than 4 with the very valid category. The application of technopreneurship learning received a positive response from students and was able to increase the entrepreneurial motivation of UNISKA Kediri students in 2020. The development of technopreneurship learning designs still needs to be carried out through a process of creativity and innovation supported by the use of learning technology in its application. To produce a technopreneurship learning output product that has high selling value, it is necessary to interact with the university and other stakeholders such as: local government, investors, industry, business organizations, and the technopreneur community.